1985
DOI: 10.1139/v85-421
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and structural studies of gallium citrate complexes

Abstract: . Can. J. Chem. 63, 2545Chem. 63, (1985. The synthesis and physical properties of two dimethylgallium citrate triester complexes are reporttd. Crystals of bis-[(trimethylcitrato)dimethylgallium(III)] are monoclinic, a = 9.839(1), b = 14.496(1), c = 11.125(1) A, P = 108.31(1)", Z = 2, space group P2]/c. The structure was solved by conventional heavy-atoms methods and was refined by full-matrix least-squares procedures to R = 0.036 and R,, = 0.037 for 1507 reflections with I 2 3u(I). The structure consists of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…2 and Table 5). The monomer units show no tendency to associate via formation of a (Ga-0)2 four-membered ring system as was found previously in the solid-state structures of numerous five-coordinate gallium complexes (3,12), or to form a polymeric chain via. weak Ga-0 bonding to the "uncoordiCan.…”
Section: Resultssupporting
confidence: 64%
“…2 and Table 5). The monomer units show no tendency to associate via formation of a (Ga-0)2 four-membered ring system as was found previously in the solid-state structures of numerous five-coordinate gallium complexes (3,12), or to form a polymeric chain via. weak Ga-0 bonding to the "uncoordiCan.…”
Section: Resultssupporting
confidence: 64%
“…The spectrum of 1 in equilibrium solutions, showed a broad (w 1/2 ) 560 Hz) asymmetric signal with a maximum at 11.84 ppm (vs AlCl 3 ) and a shoulder at a higher field. Moreover, experiments carried out in the Al(III)-citrate (1:1) system, by mixing Al(III) and citrate in 1:1 molar ratio, and adjusting the pH to neutral, revealed relatively limited changes in the 27 Al NMR spectra of the major component over time. 39b The spectral pattern of the equilibrium sample, measured on a 130.29 MHz instrument, agreed with the one described in the literature 21b for the trinuclear complex.…”
Section: Resultsmentioning
confidence: 99%
“…The samples for solution NMR studies were prepared by dissolving the crystalline complexes in D2O, at concentrations in the range 0.02-0.10 M. In D2O solutions, the pD (pH meter reading +0.40) was adjusted with concentrated DCl and NaOD solutions. NMR spectra were recorded on Bruker AM360 ( 1 H, 13 C, and 27 Al) and AM500 ( 27 Al) spectrometers. Chemical shifts (δ) are reported in ppm relative to internal DSS ( 13 C and 1 H) and external [Al(H2O)6] 3+ ( 27 Al) references.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the widespread use of gallium citrate very little structural information is available. Banta et al [14] reported the X-ray structural analysis of the trimethyl (and triethyl) ester complexes bis[(trimethylcitrato)dimethylgallium(III)] and we recently published the Xray structure of the gallium(III) citrate complex (NH 4 ) 3 [Ga(C 6 H 5 O 7 ) 2 ]·4H 2 O (1). [15] Here we present further discussion on the structure, together with a detailed NMR spectroscopic analysis of the structure both in the solid state and in solution around physiological pH.…”
Section: Introductionmentioning
confidence: 99%